Implementasi Asesmen Diagnostik Sebagai Dasar Pembelajaran Berdiferensiasi di SD Negeri 44 Cakranegara - Mohammad Archi Maulyda; Jiwandono; Nani Kusrini (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The new learning paradigm under Indonesia's Kurikulum Merdeka requires teachers to align instruction with students' characteristics, needs, and achievement levels, yet the implementation of differentiated learning in elementary schools is often constrained by the lack of systematic mapping of students' initial abilities. This study aims to analyze the implementation of diagnostic assessment as a basis for designing and delivering differentiated learning at SD Negeri 44 Cakranegara. A qualitative descriptive method with a case study approach was employed, involving one principal and four classroom teachers selected through purposive sampling. Data were collected through participatory observation, in-depth interviews, and document study, then analyzed using the Miles, Huberman, and Saldana interactive model and verified through source and technique triangulation. The results show that cognitive and non-cognitive diagnostic assessments conducted at the beginning of the school year successfully grouped 28 fourth-grade students into three learning-readiness clusters (21.4% high, 57.2% moderate, 21.4% low) and identified dominant learning styles (42.8% visual, 28.6% auditory, 28.6% kinesthetic). These mapping results were followed up by teachers through content, process, and product differentiation, although implementation remained constrained by limited time and high teacher-student ratios. The study concludes that regularly conducted diagnostic assessment plays a significant role in supporting the success of differentiated learning, enhancing active student engagement, and optimizing an inclusive learning climate, with success remaining highly dependent on institutional commitment and managerial.